Use of gamma irradiation to obtain new forms of winter wheat based on local varieties - Nazarenko, Mykola; Назаренко, Микола Миколайович; Izhboldin, Olexandr; Іжболдін, Олександр Олександрович; Izhboldina, Olena; Іжболдіна, Олена Олександрівна (Biotechnical Faculty of the University of Montenegro, 2023)
The research objective was to identify the peculiarities of the mutational activity induced by different doses of gamma irradiation in local winter wheat varieties based on the indicators of induced mutations spectrum in the second to fourth generation, to identify new high-potential forms in terms of grain productivity and quality, to identify variable components in forming such traits for a more controlled action by mutagenic agents. It has been established that a positive mutational process is essential for many useful traits, depending mainly on the original form genotype. The process has been proven to be a reliable permanent source of variability for the local genetic resources in terms of certain traits of economic value to obtain modern highly productive and highly adaptive potential forms. The regularity of the beneficial mutational process has been described, which allows to make the process of using this type of variability in order to obtain new material with the required potential more manageable, reliable and predictive. Метою дослідження було виявлення особливостей мутаційної активності, індукованої різними дозами гамма-опромінення, у місцевих сортів озимої пшениці за показниками спектра індукованих мутацій у другому-четвертому поколінні, виявлення нових високопотенційних форм у розрізі зерна. продуктивності та якості, для виявлення змінних компонентів у формуванні таких ознак для більш контрольованої дії мутагенних агентів. Встановлено, що позитивний мутаційний процес необхідний для багатьох корисних ознак, залежних головним чином від генотипу вихідної форми. Доведено, що процес є надійним постійним джерелом мінливості локальних генетичних ресурсів за певними ознаками господарської цінності для отримання сучасних високопродуктивних і високоадаптивних форм.
Використання гамма-опромінення для отримання нових форм озимої пшениці на основі місцевих сортів
Keywords: winter wheat; озима пшениця; gamma irradiation; гамма-опромінення; mutation spectrum; мутаційний спектр; mutagenesis; мутагенез